NUTRITION EDUCATION AND HEALTH SERVICES IN YOUTH ANEMIA PREVENTION AT SMA NEGERI 11 PALEMBANG - Sadiq, Ahmad; Terati, Terati (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Adolescence (10-18 years) is a period of nutritional vulnerability due to various reasons. Some research data shows that there are still nutritional problems in adolescents in Indonesia, especially the problem of nutritional anemia. The results of the 2018 Riskesdas research state that the cause of the high prevalence of nutritional anemia in adolescent girls is that they tend to go on a diet so that they can reduce their intake of nutrients, including iron. In addition, the existence of a monthly menstrual cycle is one of the factors that cause young women to be susceptible to iron deficiency anemia. Based on this, community service activities were carried out in the form of nutrition education activities (counseling) and health services in preventing anemia in adolescent girls at SMA Negeri 11 Palembang. This community service is carried out in 2 stages of activities, namely nutrition education in the form of counseling, as well as conducting health service activities in the form of screening by capturing students who have less or more nutritional status and students with indications of anemia. From anthropometric measurements, we get Most of the 60% of students with normal nutritional status for very thin and thin nutritional status were 16.7% and 3.3%, while those with nutritional status were fat and very fat as much as 6.7% and 13.3%, respectively. The results of the Hb examination showed that most of the students (66.7%) did not have anemia (Normal Hb), there were (20.%) students with moderate anemia status, and (13.3%) with mild anemia status. An increase in students' knowledge of 18.17 points after the post-test. In addition, this community service activity is expected to increase knowledge of nutrition and health, especially regarding anemia in adolescents and how to treat it.